Virus-encoded cytokine and chemokine decoy receptors. (October 2020) - Hernaez, Bruno; Alcamí, Antonio
Abstract : Poxviruses and herpesviruses encode secreted versions of cytokine receptors as a unique strategy to evade the host immune response. Recent advances in the field have shown the great impact of some of these proteins in immune modulation and viral pathogenesis, and have uncovered unique properties of these viral proteins not found in the cellular counterparts. These modifications inspired by viruses lead to improved immune modulatory activity of the soluble cytokine receptors, information that has been used to develop more efficient therapeutics to treat inflammatory conditions.